Spatial Negotiation between Patients and Caregivers in Outpatient Administrative Settings: A Design Anthropology Perspective in Regional General Hospital dr. Iskak - Silvya Bintang Ayu Candradewi; Rizka Rachmawati (Gorga : Jurnal Seni Rupa, 2026)
In the realm of healthcare facilities, accessibility is commonly perceived as a physical and technical condition, often evaluated through spatial standards and design compliance. However, such an approach tends to overlook the intricate nature of real user interactions within healthcare settings. This study endeavors to investigate accessibility as a relational and experiential process, specifically focusing on the interaction between patients, caregivers, and space within the outpatient installation of Regional General Hospital dr. Iskak. Employing a qualitative approach within a design anthropology perspective, this research utilizes limited participatory observation, visual documentation, and field notes to gather data from patients with mobility impairments and their caregivers. The analysis employs a thick description approach to interpret behavioral patterns, spatial negotiation, and user experiences in actual use settings. The findings reveal that accessibility is not an isolated individual condition but is constructed through the relational interaction between patients and caregivers. Spatial use is characterized by distributed activities, role negotiation, and adaptive behaviors in response to spatial constraints. Users actively appropriate space and reorganize spatial use to maintain comfort and coordination, indicating that accessibility emerges through everyday practices and embodied interaction. This study underscores the limitations of conventional universal design approaches, which primarily concentrate on individual users and physical standards. It proposes a shift toward contextual, interaction-based, and experience-oriented design frameworks that more accurately reflect real-use conditions. These findings contribute to expanding the comprehension of accessibility as a dynamic and relational phenomenon within healthcare environments.